Hypothyroidism - A New View On An Old Disease - Islam, Md Imtiajul; Ali, Md Zulfikar; Islam, Md Saiful; Solayman, Mohammed; Hoque, Sayama (KYAMC Journal, 2017)
Hypothyroidism is a common disorder of the endocrine system in which the thyroid gland does not produce enough thyroid hormone. Underactivity of thyroid is usually primary, from disease of thyroid, but may be secondary to hypothalamic-pituitary disease (reduced TSH drive). Untreated hypothyroidism can cause a number of health problems, such as obesity, hypertension, dyslipidaemia, infertility. The prevalence increases with age, and is higher in females than in males. Autoimmune thyroid disease is the most common aetiology of hypothyroidism. Clinical symptoms of hypothyroidism are nonspecific and may be subtle, especially in older persons. TSH and FT4 measurement are the laboratory examinations necessary for the diagnosis of hypothyroidism as well as the differential diagnosis between primary (clinical or subclinical) and secondary one. In the majority of patients, alleviation of symptoms can be accomplished through oral administration of synthetic levothyroxine, and most patients will require lifelong therapy. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 707-713